2017
DOI: 10.3201/2302.161095
|View full text |Cite|
|
Sign up to set email alerts
|

Changing Epidemiology of Hepatitis A and Hepatitis E Viruses in China, 1990–2014

Abstract: We compared the epidemiology of hepatitis A and hepatitis E cases in China from 1990-2014 to better inform policy and prevention efforts. The incidence of hepatitis A cases declined dramatically, while hepatitis E incidence increased. During 2004During -2014, hepatitis E mortality rates surpassed those of hepatitis A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…According to public health improvement, the incidence of HAV infections has been steadily decreasing as observed in China (30-fold decline of infections between 1990 and 2014). 31 The same has been earlier observed in France with a decrease of seroprevalence from 50% to 10% in 20-year-old adults between 1978 and 2000. 32 Currently, HAV endemic areas are associated with an anti-HAV IgG prevalence above 50% which corresponds to a large part of Africa as well as some areas of Asia and South America 33 ( Figure 2).…”
Section: Epidemiology and Distribution Of Genotypessupporting
confidence: 70%
See 1 more Smart Citation
“…According to public health improvement, the incidence of HAV infections has been steadily decreasing as observed in China (30-fold decline of infections between 1990 and 2014). 31 The same has been earlier observed in France with a decrease of seroprevalence from 50% to 10% in 20-year-old adults between 1978 and 2000. 32 Currently, HAV endemic areas are associated with an anti-HAV IgG prevalence above 50% which corresponds to a large part of Africa as well as some areas of Asia and South America 33 ( Figure 2).…”
Section: Epidemiology and Distribution Of Genotypessupporting
confidence: 70%
“…During Chinese public health improvements characterized by HAV decrease, HEV infections have increased 8-fold and the mortality rates have surpassed those of HAV between 2004 and 2014. 31 We can assume here that water-transmitted HEV gt1 and gt2 have progressively been replaced by other genotypes more specific to industrialized countries and associated with zoonotic transmission. Among them, HEV gt3 circulates among humans and many animals (eg, swine, rabbit, and deer) and has a worldwide distribution while gt4 circulating between humans and swine is mostly present in Southeastern Asia.…”
Section: Epidemiology and Distribution Of Genotypesmentioning
confidence: 99%
“…Owing to rapid industrialization and socioeconomic development, incidence and mortality of hepatitis A in China have undergone sharp declines, leaving hepatitis E as the most common cause of acute viral hepatitis. 3 Such an epidemiological shift is likely driven by ongoing zoonotic foodborne transmission of HEV, which has been demonstrated in swine populations across the country. In this systematic investigation of human hepatitis E infections in Shenzhen, we noted several novel features of hepatitis E in a key population center of the highly industrialized Pearl River Delta region of southern China with a large migrant population.…”
Section: Discussionmentioning
confidence: 99%
“… 2 In China, hepatitis E has overtaken hepatitis A in terms of both incidence and mortality rates over the past decade. 3 This trend is driven by a combination of factors: increasing vaccination coverage against hepatitis A, improving sanitation, and an epidemiological shift in the transmission patterns of hepatitis E.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, 1.5 million cases of hepatitis A virus (HAV) infections are reported worldwide [2], which indicated that hepatitis A remains a primary problem in hygiene and public health. Hepatitis A has a very similar clinical symptom compared to hepatitis E. Except for the severer pathological injuries of hepatitis E than that of hepatitis A, both of two are self-limiting diseases, do not lead to liver cirrhosis and liver cancer, and transmit via orofecal route and personto-person contact [4]. Consequently, HAV-contaminated water, vegetables, fruits, blood products, and other foodstuffs, especially undercooked shellfish including clams, oysters, and mussels (Figure 1) [5,6], are the major pathways of infections with hepatitis A [7,8].…”
Section: Introductionmentioning
confidence: 99%